Anaerobic co-digestion of fruit and vegetable wastes with different substrates - Rizk, M. C. [UNESP]; Bergamasco, R.; Tavares, C. (Taylor & Francis, 2015)
Anaerobic biological treatment of organic solid wastes can be an acceptable alter- native to current disposal strategies. Therefore, the aim of the present study was to evaluate the anaerobic biodegradability potential of fruit and vegetable wastes (FVW) using different co-substrates. The FVW were shredded, blended and diluted with water, domestic sewage, sewage sludge and swine waste in concentrations that varied from zero to 40%. The experiments were conducted in glasses bottles of 100 ml, 25°C, in a shaker at 150 rpm during 60 days. After analyzing the monitored parameters, it can be said that the best results had been obtained when the FVW had been diluted with high proportions of domestic sewage and swine waste. In these conditions, the chemical oxygen demand removal was superior to 60%, the final C/N ratio had significant reduction and the biogas production was close to 0.40 m3kg−1 of total volatile solids.